Anaesthesiology and intensive care Possibilities of modification of risk factors for ventilator-associated pneumonia in cardiac surgery patients - Wróblewska, Marta; Stępniak, Agata; Burnos, Zbigniew; Kania-Pudło, Marta; Leszczyński, Piotr; Hendzel, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Patients undergoing cardiac surgery require intensive care, the quality of which may significantly reduce the risk of postoperative complications in this patient group. Factors which decrease the risk of ventilator-associated pneumonia (VAP) include care provided to intubated and mechanically ventilated patients, maintenance of a semirecumbent position with elevation of the chest, enteral feeding, prevention of oropharyngeal colonization, and the use of sucralfate instead of H2 receptor antagonists in the prophylaxis of stress ulcers of the stomach. Similarly to other forms of nosocomial infections, the main element of VAP prophylaxis is proper hand hygiene of healthcare workers.